KAJIAN RELIABILITAS DAN AVAILABILITAS PADA SISTEM KOMPONEN PARALEL - Pradewi, Riana Ayu Andam; Sudarno, Sudarno; Suparti, Suparti (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2014)
Reliability and availability are a measure of item or system performance. System reliability and system availability obtained from the calculation of reliability and availability of the components in the system. Reliability of components in the system are affected by the time to failure (TTF). While the availability of components in the system are affected by the mean time to failure (MTTF) and mean time to repair (MTTR). Given observed time data of lifting machines consists of trolley drive and hoist in parallel, is measured its system availability. Parameter values determined using simple linear regression and maximum likelihood estimation. Furthermore observation time test data distributions in the Kolmogorov-Smirnov test. Trolley drive has exponential distribution for failure time data with while repair time data is normal distribution with and . Hoist has weibull failure time data with and while lognormal repair time data has and . The higer value of ti,system reliability value will be close to 0 and the engine can survive until the specified time. Due to MTTF is 4000 hours and MTTR is 45,70 hours, trolley drive’s availability is 98,87%. Availability of hoist is 98,84% from MTTF is 5821,61 hours and MTTR is 67,80 hours. The parallel system availability is 99,986% means the probability of system is in the state of functioning at given time is 99,986%.